AGRICULTURAL WATER MANAGEMENT THROUGH MAGNETIZATION OF IRRIGATION AND DRINKING WATER: A REVIEW - GILANI, A.; KERMANSHAHI, H.; GHOLIZADEH, M.; GOLIAN, A. (Journal of Aridland Agriculture, 2017)
Received 03 December 2017; Accepted 18 February 2018 *Corresponding Author M. Gholizadeh Department of Chemistry, Faculty of Science, Ferdowsi University of Mashhad, Mashhad, Iran Email: m_gholizadeh@um.ac.ir ©This article is open access and licensed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/) which permits unrestricted, use, distribution and reproduction in any medium, or format for any purpose, even commercially provided the work is properly cited. Attribution — You must give appropriate credit, provide a link to the license, and indicate if changes were made. Agricultural water management in arid and semi-arid countries such as Iran is of utmost importance. Alterations of water as a major component of each bio system through magnetization have been reviewed in this study. Magnetization process has been used as green technology in industry and agriculture with controversial results. Properties of water such as pH, hydrogen bonds, temperature, structure and its ions can be affected by an external magnetic field. Subsequent modifications have substantial impacts on water quality that is determined for optimum plant and animal production. There are some reports among numerous studies in agronomy, gardening and animal husbandry which claim fruitful influence of this treatment both qualitatively and quantitatively. Nevertheless, there are some controversial reports on the effects of magnetization. In conclusion, the response of organisms depends on magnetization time and intensity, water quality and plant or animal species. These variables should be taken into account for further studies regarding this mysteries process.